Production of Structural and Nonstructural Lightweight Concrete Using Slate and Plastic Waste - Murad Khan; Muhammad Haris Javed; Khuda Bukhsh; Umair Sajjad; Hamza Umar (Journal of ICT, Design, Engineering and Technological Science, 2022)
Concrete is a construction material that is widely used in the world. In the design of concrete structures, lightweight concrete plays a vital role to decrease the density or a dead load of structural elements. This paper investigates the utilization of slate aggregate as a coarse aggregate replacement and the replacement of plastic waste with fine aggregate for the production of lightweight concrete. The research aims to get the structural and nonstructural lightweight concrete by replacing the lightweight aggregate and evaluate their effects on compressive strength, density, and acidic attack. Before the preparation of concrete for the experiment, different tests were conducted to find out the physical properties of the materials. A concrete mix ratio of 1:1:2 and 0.45 w/c ratio was used for our experiment. Coarse aggregate is replaced by slate aggregate from 80% to 100% replacement and sand is replaced by plastic waste from 50 to 60%. By conducting a compressive strength test, the observed optimum value for structural lightweight concrete was 3105 psi in the case of replacing slate 100% with coarse aggregate and plastic waste 50% with fine aggregate. By replacing 80% of slate with coarse aggregate and 60% of plastic waste with fine aggregate, the optimum value for non-structural lightweight concrete was 2841 psi.